2004
DOI: 10.1051/agro:2003056
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of flag leaf and ear photosynthesis with biomass and grain yield of durum wheat under various water conditions and genotypes

Abstract: -Photosynthetic activity of cereals has traditionally been studied using leaves, thus neglecting the role of other organs such as ears. Here, we studied the effects of water status and genotypes on the photosynthetic activity of the flag leaf blade and the ear of durum wheat. The various parameters related to the photosynthetic activity were analysed in relation to the total above-ground plant biomass and grain yield at maturity. Four local varieties plus two cultivars adapted to the semiarid areas of South Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(70 citation statements)
references
References 33 publications
3
65
0
2
Order By: Relevance
“…It is generally thought that grain filling in wheat is not limited by source (assimilate) supply to the developing grain under mild growing conditions, but assimilate supply can become limiting under conditions such as drought or heat that reduce photosynthetic capacity (Abbad et al 2004). Under nonstress conditions, flag leaf photosynthesis contributes a significant proportion of the assimilates used in grain filling (e.g.…”
Section: Chlorophyll Content and Functionalitymentioning
confidence: 99%
“…It is generally thought that grain filling in wheat is not limited by source (assimilate) supply to the developing grain under mild growing conditions, but assimilate supply can become limiting under conditions such as drought or heat that reduce photosynthetic capacity (Abbad et al 2004). Under nonstress conditions, flag leaf photosynthesis contributes a significant proportion of the assimilates used in grain filling (e.g.…”
Section: Chlorophyll Content and Functionalitymentioning
confidence: 99%
“…For a winter wheat stand in China, [81] found that at an fAW below 50%, the plants experienced "water stress", and stomatal conductance (gc) was decreasing linearly with fAW. Reports on the overall contribution of ear activity differ [82][83][84]. However, it was shown that the rate of ear photosynthesis can exceed that of the flag leaf, especially under water stress conditions [83,85].…”
Section: Suitability Of Model-temperature Combinations To Predict Submentioning
confidence: 99%
“…Reports on the overall contribution of ear activity differ [82][83][84]. However, it was shown that the rate of ear photosynthesis can exceed that of the flag leaf, especially under water stress conditions [83,85]. Thus, under the observed moisture and phenological conditions, ears probably remain active for a longer time period and maintain a higher water content than flag leaves [84,86,87].…”
Section: Suitability Of Model-temperature Combinations To Predict Submentioning
confidence: 99%
“…Physiological and microbiological responses of higher plants to environment have been studied extensively over the world, especially by targeting model plants and crop plants [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Abiotic stresses in environment are linked with all the living process of higher plants and greatly influence plant productivity developmental cues and environmental stimuli, most of which are the important factors affecting eco-environment such as low temperature, drought, salinity and UV-B radiation, which often occur in terrestrial ecosystem.…”
Section: Introductionmentioning
confidence: 99%